2016
DOI: 10.1186/s12884-016-0835-x
|View full text |Cite
|
Sign up to set email alerts
|

Linear trends and seasonality of births and perinatal outcomes in Upper East Region, Ghana from 2010 to 2014

Abstract: BackgroundSeasonal variations greatly influence birth patterns differently from country to country. In Ghana, there is paucity of information on birth seasonal patterns. This retrospective study described the trends and seasonality of births and perinatal outcomes in Upper East Region of Ghana.MethodsBirths occurring in each month of the calendar years (2010–2014; inclusive) were extracted from the District Health Information Management System (DHIMS2) database of the Bolgatanga Municipal Health Directorate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(35 reference statements)
1
8
1
Order By: Relevance
“…We find, consistent with the animal ethology and evolutionary ecology literature, that local energy availability evaluated by way NDVI to be positively associated with monthly birth pulses. Although a relationship between precipitation and temperature on monthly birth pulses in humans has been found in past studies (Condon & Scaglion 1982;Lam & Miron 1998;Lawlor et al 2005;Torche & Corvalan 2010;Osei et al 2016), here we find that they have no significant effect on birth seasonality; however, both are indirectly related to it through their combined impact on NDVI.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…We find, consistent with the animal ethology and evolutionary ecology literature, that local energy availability evaluated by way NDVI to be positively associated with monthly birth pulses. Although a relationship between precipitation and temperature on monthly birth pulses in humans has been found in past studies (Condon & Scaglion 1982;Lam & Miron 1998;Lawlor et al 2005;Torche & Corvalan 2010;Osei et al 2016), here we find that they have no significant effect on birth seasonality; however, both are indirectly related to it through their combined impact on NDVI.…”
Section: Discussioncontrasting
confidence: 67%
“…Local energy availability is impacted by a number of bio-physical factors, including temperature and precipitation (Wu et al 2001;Pettorelli 2013;Yan et al 2015;Gilbert 2019). Not surprisingly, a large body of research has linked seasonal variation in precipitation and temperature to birth seasonality in humans (Condon & Scaglion 1982;Lam & Miron 1998;Ellis et al 2005;Lawlor et al 2005;Torche & Corvalan 2010;Osei et al 2016). However, these aspects of climate serve as proxy variables for local energy availability (Pettorelli 2013) and no one has examined the direct impact of local energy availability on human birth seasonality.…”
Section: Introductionmentioning
confidence: 99%
“…However, the parity of infants was dependent on the season, with uniparae being most common in autumn. The dependence of parity on the season has been recognised previously, the pattern of which alters according to the social and temporal background of the region 39 40 . We found seasonality to be a significant variable in infant nighttime sleep duration even after adjustment for parity (data not shown), suggesting that any influence of season-specific parity is likely to be minimal.…”
Section: Discussionmentioning
confidence: 79%
“…Numerous studies have assessed the relationship between season and adverse birth outcomes. [13][14][15][16][17][18][19][20][21] These studies have typically focused on the seasonality of preterm birth and birth weight, whereas fewer studies have examined the relationship between season and less common adverse birth outcomes like stillbirth. 22 Several small studies have been conducted in sub-Saharan Africa, where adverse birth outcomes may be more tightly linked to distinct rainy and dry seasons and related agricultural cycles, 16 18 20 21 and one meta-analysis of studies conducted in East Africa found an increased risk of preterm birth during the rainy season.…”
Section: Open Accessmentioning
confidence: 99%